2022
DOI: 10.1108/ribs-10-2021-0136
|View full text |Cite
|
Sign up to set email alerts
|

Institutional quality, unemployment, economic growth and entrepreneurial activity in developed countries: a dynamic and sustainable approach

Abstract: Purpose This paper aims to analyse the impact of institutional quality, economic factors and unemployment on entrepreneurial activity. The dynamic approach adopted in this study permits to evaluate the simultaneous influence of specific factors on total entrepreneurial activity. Design/methodology/approach A quantitative approach through a panel vector autoregression analysis was adopted to take into account possible endogeneity issues, and a short-run Granger test was used to test causality between variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 91 publications
1
12
1
Order By: Relevance
“…This evidence underscores the need for contextspecific assessments of variables related to institutional theory's cognitive-cultural, normative and regulatory dimensions in both developed and developing countries. We also acknowledge that the greater effectiveness of institutions on TEA in developed countries Institutions and entrepreneurial activities can be attributed to the quality of the institutions in these countries (Ragmoun, 2023;Audretsch et al, 2023b). Firstly, in Model 1, where we examined the impact of cognitive-cultural institutions, we found support for 3 out of 8 variables in developed countries and 2 in developing economies.…”
Section: Theoretical Implicationsmentioning
confidence: 72%
See 4 more Smart Citations
“…This evidence underscores the need for contextspecific assessments of variables related to institutional theory's cognitive-cultural, normative and regulatory dimensions in both developed and developing countries. We also acknowledge that the greater effectiveness of institutions on TEA in developed countries Institutions and entrepreneurial activities can be attributed to the quality of the institutions in these countries (Ragmoun, 2023;Audretsch et al, 2023b). Firstly, in Model 1, where we examined the impact of cognitive-cultural institutions, we found support for 3 out of 8 variables in developed countries and 2 in developing economies.…”
Section: Theoretical Implicationsmentioning
confidence: 72%
“…For example, Charfeddine and Zaouali (2022) conducted a panel data analysis for 2001-2018. A similar situation exists in Ragmoun's (2023) research, which involves a panel data analysis for 1996-2019. In this study, Ragmoun (2023) worked on a sample from 24 developed countries and found a significant and positive impact only for four years between unemployment rates and entrepreneurial activities.…”
Section: Theoretical Implicationsmentioning
confidence: 75%
See 3 more Smart Citations